An analysis of traditional Thai paintings depicting demon Mara’s Assault applying Rasa theory of aesthetics - Jumsai Na Ayudhya, Subhachog (DEC Journal : Art and Design, 2023)
This article proposes an analysis of traditional Thai paintings depicting demon Mara’s Assault—Mara attempting to tempt Buddha, applying “Rasa”, an Indian concept of sentiment, one of significant theories in Indian aesthetics. It outlines the origin and the concept of Rasa, then examines Buddhist literatures describing the Temptation of Buddha by Mara scene, from which such paintings are originated and portrayed. Then, it provides an explanation on the paintings in details where they correspond to the various Rasas and eventually analyses each part of the paintings: how they interrelate, how a Rasa gives rise to one another, and how it shifts or transform. The article aims to deepen understanding on the representation of the scene and to provide some guidelines on applying the Rasa aesthetics theory into creation or further analysing other Thai traditional paintings.